Examining the impact of debt on investment for Austrian non-financial sectors and firms - Dlugosch, Dennis (OECD Publishing, 2021)
Using a micro-level model of investment, this paper finds that firm-debt and investment are negatively associated across firms in Austrian manufacturing industries. The finding is robust to various changes to the model specification. Moreover, in an extension of the basic model, different components of debt are examined, pointing out that debt owed to banks and long-term debt have a stronger negative effect than other forms of debt. Comparisons with investment models estimated for other European countries suggest that the impact of debt on investment is more negative in Austria than elsewhere. Results from interaction models of debt owed to banks with an index of credit easing show that firms in industries which are more bank-dependent invest relatively more than firms in industries that are less bank-dependent after an easing of credit conditions
Keywords: Economics; Austria